Adolescents at the STD sector of the Universidade Federal Fluminense - Isolan, Tomaz B. (2001)
Introduction: The relevance of STDs for the teenage age group manisfests itself due to the increasing precocity of sexual relations, the increase in the number of sexual partners and the lack of constancy in the use of preservatives. OMS data report an increase in the frequency of STDs among teenagers. One third of all STDs occur in this age group, and one adolescent in four contracts an STD before becoming an adult. Objective: To describe the care given to teenagers of both sexes at the STD Sector of the Universidade Federal Fluminense during the year 1995. Methodology: Data were collected from a analysis of all teenage patient records seen at the STD Sector on 1995. Data collected included: sex; age; age at the first sexual relation; color; marital status; residential district; contraceptive use and method; how the patient was referred to the Sector; profession; fidelity to the partner; number of visits to the Sector; number of gestations; chief complaint; previous STDs and diagnosed disease. Results: In 1995, of the 1187 patients seen at the STD Sector, 201 were teenagers - 16.9% of the total; 3 were children - 0.2% of the total. The rest were adults - 82.9%. Among the teenagers, 57 were male (28.4%) and 144 female (71.6%). Of all adolescents, 44.6% lived in the city of Niterói, 43.2% in the city of São Gonçalo and 12.2% lived in other districts of the state of Rio de Janeiro. The median age at the time of the first sexual relation was 14.3 years. 73% reported having only one partner (45% of the male and 84.4% of female adolescent patients). Friends and other patients referred 28.7% of all teenagers to the Sector; doctors from private clinics referred 4.2% of the total (12.8% of male and 0.8% of female patients). Concerning contraceptive use, 35.2% of the girls reported not using any method; 22.8% used oral contraceptives and 13.8% were pregnant. Only 10.5% of the girls reported condoms were routinely used for their sexual relations; 86% informed condoms were not used. 8 female adolescents reported having had an abortion. Of all teenagers, 2.7%, all of them female, informed having been victims of sexual violence. 6% reported previous genital infection, being 5 cases of syphilis and 3 of gonorrhoea. 32% of all female adolescents sought medical care at the Sector for vaginal discharge; 35% of the male adolescents for urethritis. 57% of the girls had vulvovaginitis diagnosed, 9.6% HPV infection, 9% syphilis, 3.6% gonorrhoea and one of them was HIV-positive. 11 female patients had more than one genital infection. 23.9% of the male adolescents had gonorrhoea, 20.7% HPV infection, 10.4% syphilis. None was HIV-positive. The return rate was 58%. Conclusion: The total of 201 teenagers represented 16.9% of all patients seen in 1995. The majority (55.4%) of teenagers were from outside the district of Niterói; 51.3% were students; 30.8% workers; 32.5% of all teenagers did not use any contraceptive method; 8.3% reported being virgin; 86% denied using preservatives; 13.9% of the female adolescents were pregnant at the time of the first visit to our Sector; 2.7% of the girls reported having been victims of sexual violence; the most common diagnosis was vulvovaginitis among females and urethritis among males; 10% of the female and 17.3% of the male teenagers presented no genital infections. As many did not have clinical STDs or other infections the return rate of 58% was considered excellent.